The starseekers - Glover, Nicole (Glover, Nicole. Murder & magic, 2026)
The race to space was on, and the Moon was what everyone had their eyes on. Including Cynthia Rhodes, a brilliant arcane engineer at NASA's Ainsworth Research Labs. Talented in math and magic, she hosts a magical educational show... a job she took mostly for a chance to regularly see the dashing Theodore Danner, a professor of arcane archeology. When a cursed museum curator nearly interrupts a broadcast of their show, Cynthia finds an eager sleuthing partner in Theo.